Outcome of children and adolescents with relapsed Hodgkin lymphoma treated with high-dose therapy and autologous stem cell transplantation: the Memorial Sloan Kettering Cancer Center experience. Issue 8 (3rd August 2018) - Giulino-Roth, Lisa; O'Donohue, Tara; Chen, Zhengming; Trippett, Tanya M.; Klein, Elizabeth; Kernan, Nancy A.; Kobos, Rachel; Prockop, Susan E.; Scaradavou, Andromachi; Shukla, Neerav; Steinherz, Peter G.; Moskowitz, Alison J.; et al.
Abstract: To evaluate outcomes and prognostic markers among children with relapsed Hodgkin lymphoma (HL) treated with autologous stem cell transplant (ASCT), we conducted a retrospective analysis of 36 consecutive pediatric patients treated at Memorial Sloan Kettering Cancer Center from 1989 to 2013. With a median follow-up of 9.6 years, the 10-year overall survival (OS) and event-free survival (EFS) were 74.1 and 67.1% respectively. Absence of B-symptoms, chemotherapy-sensitive disease, and transplant date after 1997 were each associated with superior EFS [HR 0.12 ( p = .0015), 0.18 ( p = .0039), and 0.17 ( p = .0208), respectively]. Childhood Hodgkin International Prognostic Score at relapse (R-CHIPS) was calculated in a subset of patients ( n = 22) and a lower score was associated with improved OS (HR 0.29, p = .0352) and a trend toward improved EFS (HR 0.38, p = .0527). In summary, ASCT results in durable remission for the majority of pediatric patients with relapsed HL. R-CHIPS should be evaluated in larger cohorts as a potential predictive tool.